2015
DOI: 10.1186/s13104-015-1690-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge and practices on infant teething, Taif, Saudi Arabia

Abstract: BackgroundParents’ false beliefs about signs and symptoms associated with teething have been documented in many studies around the world. This study was conducted to assess parental knowledge on infant teething process and to investigate parents’ practices used to alleviate teething disturbances.MethodsA cross-sectional survey was conducted among parents of children of 6 months–5 years old in Taif, Saudi Arabia during April 2013. Convenience method of sampling was adopted and the data was collected by mean of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
(26 reference statements)
1
20
1
5
Order By: Relevance
“…Knowledge of the parents was not found to be associated with the socioeconomic status. Similar findings were reported by Elbur et al 14 However, another Indian study reported contrasting results. 7 Knowledge regarding infant care is influenced by the advice of elderly and the level of education does not necessarily influence knowledge.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Knowledge of the parents was not found to be associated with the socioeconomic status. Similar findings were reported by Elbur et al 14 However, another Indian study reported contrasting results. 7 Knowledge regarding infant care is influenced by the advice of elderly and the level of education does not necessarily influence knowledge.…”
Section: Resultssupporting
confidence: 88%
“…Other studies reported contrasting finding. 14 An alarming fact showed by the present study was that the parents were unaware that delayed eruption could be the sign of underlying systemic disease. Certain nutritional deficiencies, hypopituitarism and hypothyroidism, can result in delayed tooth eruption.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…There are also results which showed a wide gap in knowledge and misconceptions with regards to the ascribed signs and symptoms and practices used to manage infant teething problems. 35 Aside from teething signs and symptoms, there has been a number of recommended options suggested for management and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, "blistering, placing leeches on the gums, and cauterization of the back of the head were the treatment options reported by the parents for teething" 5 . Mothers usually use systemic and topical analgesics to relieve teething pain and antibiotics to treat associated symptoms 6 . Moreover, they have their children bite objects to alleviate symptoms 7 .…”
Section: Introductionmentioning
confidence: 99%